Becoming Visible: The Role of the Internet in Dress Choices among Native-Born Converts to Islam in North America - Akou, Heather (Hawwa, 2015)
Although hijab is just one facet of Islam (and from a theological perspective, not the most important), many native-born converts in North America—especially women—appear to struggle with it: what to wear; what to think about hijab; how to make the transition and how it affects their interactions with non-Muslims, including employers, close friends and family members. How can converts align their appearance with the values of their faith, especially in the context of negative stereotypes following 9/11? Much like patients with rare medical disorders, converts living outside the Dar al-Islam can use the Internet to overcome isolation and a lack of local support. This chapter will consider the kinds of resources available through the Internet, particularly blogs, videos, retail websites and multi-user “boards”. Data for this chapter comes from my own experience with conversion to Islam as well as an ongoing virtual ethnography concerning the growing Islamic fashion industry.